Does Psychological Capital Mediate the Relationship Between Transformational Leadership and Adaptive Performance of Civil Servant? - Dewi, Kari Septiana; Soeling, Pantius Drahen (Technium Social Sciences Journal, 2024)
The Fourth Industrial Revolution (4.0) and the advent of the Society 5.0 era, have ushered us into a VUCA (volatility, uncertainty, complexity, and ambiguity) environment. The adaptability of employees has become paramount, necessitating organizations to focus on managing and enhancing adaptive performance alongside routine task completion. Consequently, employee adaptive performance has emerged as a critical aspect of human resource management in both private and public sectors. This study aims to explore the relationship between transformational leadership, psychological capital, and adaptive performance, drawing on the Conservation of Resources Theory and Self-Determination Theory. Additionally, the research seeks to address whether psychological capital mediates the connection between transformational leadership and adaptive performance. Utilizing questionnaire data collected from 317 civil servants at the Ministry of Communication and Informatics of the Republic of Indonesia, the results reveal that 1) transformational leadership does not significantly impact adaptive performance, 2) psychological capital significantly and positively influences adaptive performance, 3) transformational leadership significantly and positively affects psychological capital, and 4) psychological capital fully mediates the relationship between transformational leadership and adaptive performance. These findings contribute to the development of a theoretical framework for fostering adaptive performance in public sector organizations and offer a fresh perspective in human resource management.